Secretoglobin 3A2 protects lung from developing cigarette smoke-induced pulmonary emphysema. (April 2023) - Kurotani, Reiko; Ono, Sotaro; Miyano, Yuki; Nakayama, Shun; Liu, Huaitian; Aibara, Daisuke; Sakahara, Satoshi; Sato, Masamichi; Sato, Kento; Inoue, Sumito; Shibata, Yoko; Lee, Maxwell P.; et al.
Abstract: Secretoglobin (SCGB) 3A2 is a bioactive molecule exhibiting various functions such as improving allergic airway inflammation and pulmonary fibrosis and promoting bronchial branching and proliferation during lung development. To determine if and how SCGB3A2 is involved in chronic obstructive pulmonary disease (COPD), a multifactorial disease with both airway and emphysematous lesions, a COPD mouse model was created by exposing Scgb3a2 -deficient (KO), Scgb3a2- lung-specific overexpressing (TG), and wild type (WT) mice to cigarette smoke (CS) for 6 months. The KO mice showed loss of lung structure under control condition, and CS exposure resulted in more expansion of airspace and destruction of alveolar wall than WT mouse lungs. In contrast, TG mouse lungs showed no significant changes after CS exposure. SCGB3A2 increased the expression and phosphorylation of signal transducers and activators of transcription (STAT)1 and STAT3, and the expression of α1-antitrypsin (A1AT) in mouse lung fibroblast-derived MLg cells and mouse lung epithelial-derived MLE-15 cells. In MLg cells, A1AT expression was decreased in Stat3 -knockdown cells, and increased upon Stat3 overexpression. STAT3 formed a homodimer when cells were stimulated with SCGB3A2. Chromatin immunoprecipitation and reporter assays demonstrated that STAT3 binds to specific binding sites on the Serpina1a gene encoding A1AT and upregulates its transcription in lung tissues of mice. Furthermore, nuclear localization of phosphorylated STAT3 upon SCGB3A2 stimulation was detected by immunocytochemistry. These findings demonstrate that SCGB3A2 protects the lungs from the development of CS-induced emphysema by regulating A1AT expression through STAT3 signaling.